2013
DOI: 10.1093/carcin/bgt290
|View full text |Cite
|
Sign up to set email alerts
|

Dietary heme iron and the risk of colorectal cancer with specific mutations in KRAS and APC

Abstract: Red meat intake has been linked to increased colorectal cancer (CRC) risk. Although the underlying mechanisms remain unclear, experimental studies suggest a role for dietary heme iron. Because heme iron was shown to promote specific mutations, it would be insightful to link heme iron data to CRC with mutations in key genes in an observational, population-based study. We investigated the association between dietary heme iron intake and risk of CRC with mutations in APC (adenomatous polyposis coli) and KRAS (Kir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…Jakszyn and others () demonstrated a potential association between higher intakes of heme iron and the risk of esophageal adenocarcinoma. Gilsing and others () studied the interrelationship between dietary heme iron and the risk of colorectal cancer with specific mutations in Kristen‐ras (KRAS) and adenomatous polyposis coli (APC), and they observed a positive association between heme iron intake and risk of colorectal cancer with the activating G > A mutation in KRAS and overall G > A mutation in APC.…”
Section: Postprandial Heme Iron‐induced Toxicitymentioning
confidence: 99%
“…Jakszyn and others () demonstrated a potential association between higher intakes of heme iron and the risk of esophageal adenocarcinoma. Gilsing and others () studied the interrelationship between dietary heme iron and the risk of colorectal cancer with specific mutations in Kristen‐ras (KRAS) and adenomatous polyposis coli (APC), and they observed a positive association between heme iron intake and risk of colorectal cancer with the activating G > A mutation in KRAS and overall G > A mutation in APC.…”
Section: Postprandial Heme Iron‐induced Toxicitymentioning
confidence: 99%
“…Heme is more bioavailable and readily absorbed as compared to non-heme. However, detrimental effects are associated with heme specifically, which includes cytotoxicity and the increased formation of endogenous N -nitroso compounds (NOCs), which may increase the overall mutation rate in the DNA of colonic tissue [55,56,57]. Heme in red meat may catalyze the production of endogenous NOCs within the colon and thereby catalyze the formation of cytotoxic and genotoxic aldehydes by lipoperoxidation [43,44,51,56].…”
Section: High Heme Intake Is Associated With Increased Risk Of Cancermentioning
confidence: 99%
“…In a recent study, a molecular genetic epidemiological approach was used to understand the association between heme iron intake and colorectal cancer risk by examining specific mutations in colon tumors in the adenomatous polyposis coli (APC) tumor suppressor gene and Kirsten ras (KRAS) oncogene [26]. In this nested case-control study, no difference was found between cases and controls in daily heme intake in women.…”
Section: Endogenous Compoundsmentioning
confidence: 99%